2017
DOI: 10.3892/etm.2017.4594
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of prefrontal lobes in patients with major depression disorder using a dual-mode technique of 3D-arterial spin labeling and 18F-fluorodeoxyglucose positron emission tomography/computed tomography

Abstract: The aim of this study was to explore the functions of cerebral blood perfusion and glucose metabolism in the prefrontal lobe of patients with major depression disorder (MDD), and to analyze the correlations between these functional changes and depressive symptoms. 3D-arterial spin labeling (ASL) and 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) were successfully performed in 17 patients with MDD and 16 healthy controls in a resting state. The depressive symptoms of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The l-DLPFC, which plays an important role in the implementation of cognitive control, had increase of Oxy-Hb response to Stroop interference, which corresponds to the results of previous studies including our own 4 , 5 , 30 , 55 , 56 . Besides, the l-DLPFC was reported to implicate in mood regulation in mood disorders, demonstrating significant coincidence between running-induced positive mood and l-DLPFC activation as we hypothesized 19 – 21 . The right DLPFC, which is involved in conflict resolution (faster reaction time after incongruent trials) and Stroop accuracy, was also showed significant activation 31 , 57 , 58 .…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The l-DLPFC, which plays an important role in the implementation of cognitive control, had increase of Oxy-Hb response to Stroop interference, which corresponds to the results of previous studies including our own 4 , 5 , 30 , 55 , 56 . Besides, the l-DLPFC was reported to implicate in mood regulation in mood disorders, demonstrating significant coincidence between running-induced positive mood and l-DLPFC activation as we hypothesized 19 – 21 . The right DLPFC, which is involved in conflict resolution (faster reaction time after incongruent trials) and Stroop accuracy, was also showed significant activation 31 , 57 , 58 .…”
Section: Discussionmentioning
confidence: 62%
“…The right DLPFC, which is involved in conflict resolution (faster reaction time after incongruent trials) and Stroop accuracy, was also showed significant activation 31 , 57 , 58 . The right-VLPFC, which is associated with mood and emotion regulation, was observed to have significant activation coinciding with increased arousal and pleasure levels 19 – 21 , 59 . In addition, the FPA, a brain region which generally activates with the DLPFC to response to tasks involving manipulation and monitoring, such as planning for action, was observed to have significant both sides activation 60 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This could play an additional role in the inconsistent findings of the prefrontal regions. A recent study investigating CBF and glucose metabolism in MDD observed glucose metabolism to be more sensitive than CBF in identifying functional abnormalities in the frontal lobes [34]. Perfusion, neuronal activity, and metabolism of a given region may inform or influence each other.…”
Section: Limitationsmentioning
confidence: 99%
“…fNIRS and fMRI studies found that MDD patients in remission exhibited reduced cerebral responses and functional abnormalities specifically in the left PFC, suggesting that dysfunction in the frontal lobe may be a specific trait marker for depression [58,73]. Fu et al studied MDD patients using PET and reported diminished cerebral blood flow and glucose metabolism in the prefrontal lobes as well as attenuated glucose uptake in the frontal and temporal lobes [74,75]. Likewise, a singlephoton emission computerized tomography (SPECT) study found lower perfusion in the PFC in patients with depression and established an association between hypofrontality in the frontotemporal cortices and a poor response to treatment in patients with depression [76,77].…”
Section: Discussionmentioning
confidence: 99%